The Out-of-Network Benefit: Problems and Policy Solutions - Kelly A. Kyanko; Susan H. Busch (SAGE Publishing, 2012)
Health insurance plans that include coverage for out-of-network providers are common and have the potential to reduce health care costs and even improve quality. Yet, consumers may be exposed to significant unexpected and unreasonable out-of-pocket costs due to lack of accurate information on network participation, nontransparent out-of-pocket costs, inadequate provider networks, involuntary use of out-of-network emergency care, and use of out-of-network providers at in-network hospitals. Although the Affordable Care Act and some states provide some consumer protections, these may not be adequate.